The effect of a program based on the SCAMPER strategy in developing some health skills for second-grade students in science (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The research aimed to identify the effect of a program based on the SCAMPER strategy in developing some health skills for second-grade students in science, and to investigate the effect of the gender variable for students in the experimental group on their acquisition of health skills. To address the research problem, a health skills scale was used that contained (15) questions. The research sample included (63) male and female students from the second grade of basic education, and the descriptive approach was used. To judge the validity of the scale, it was presented to a group of (7) specialized arbitrators in the College of Education. At Tishreen University, its stability was confirmed by applying it to a survey sample, by calculating the Pearson coefficient, which was (0.946).The research ended with the following results:-There are statistically significant differences between the average scores of the experimental and control groups in favor of the experimental group in the post-application.- There are statistically significant differences between the average scores of the experimental group in the pre- and post-applications in favor of the post-application.-There are no statistically significant differences between the average scores of the experimental group in the post-application due to the gender variable.